Faktor yang Mempengaruhi Kejadian Hiperemesis Gravidarum di Klinik Pratama Vina Kota Medan Provinsi Sumatera Utara - Siska Suci Triana Ginting; Rumondang Sitorus; Imarina Tarigan; Rohhasianti Sagala; Herly Arta Oktaviana; Dina Sandriana (PPNI UNIMMAN, 2025)
Hyperemesis gravidarum is a condition of excessive nausea and vomiting during pregnancy, which can lead to dehydration, weight loss, potassium deficiency (hypokalemia), and serious metabolic disorders. If left untreated, this condition can trigger complications such as ketosis, liver dysfunction, and even death. The exact cause is unknown, but several predisposing factors, such as multiple pregnancies, hydatidiform moles, psychological conditions (such as stress, fear of pregnancy), and a decreased immune system in pregnant women, are believed to play a role (Maryunani, 2018). Persistent nausea and vomiting cause the body to use carbohydrate and fat reserves for energy, which produces toxic metabolites. As a result, body tissues receive fewer nutrients and oxygen. Furthermore, potassium loss through vomiting and urine can contribute to hypokalemia and worsen vomiting. According to Maryunani (2019), this condition occurs more frequently in 60–80% of primiparous pregnant women and 40–60% of multiparous pregnant women during the first trimester. This study used an analytical method with a cross-sectional approach to determine the relationship between knowledge and attitudes of pregnant women towards the occurrence of hyperemesis gravidarum. The results showed a significant relationship between knowledge (p = 0.015) and attitudes of pregnant women (p = 0.006) towards the occurrence of hyperemesis gravidarum. It is hoped that health workers, especially in Community Health Centers, will be more active in providing education to pregnant women regarding the prevention of hyperemesis gravidarum. Pregnant women are also expected to regularly check their pregnancies and seek appropriate information to maintain their health during pregnancy. This study used an analytical method with a cross-sectional approach to determine the relationship between knowledge and attitudes of pregnant women towards the occurrence of hyperemesis gravidarum. The results showed a significant relationship between knowledge (p = 0.015) and attitudes of pregnant women (p = 0.006) towards the occurrence of hyperemesis gravidarum.